Advancements in hydrogen generation, storage, and utilizations: A comprehensive review of current trends in Bangladesh - Shovon, Shaik Muntasir; Akash, Faysal Ahamed; Rahman, Md Abdur; Rahman, Wahida; Chakraborty, Prosenjeet; Monir, Minhaj Uddin; Sarkar, Shaheen M.; Azrina, Abd Aziz; Chowdhury, Shahariar (Elsevier, 2024)
Bangladesh is a developing country heavily reliant on fossil fuels, which emits toxic gases during its combustion. In that scenario, hydrogen is an eco-friendly fuel source with a calorific value of 120 MJ/kg which is significantly higher than fossil fuels. With a density of 0.09 kg/m3 at 273 K, hydrogen is just 1/14th that of air. Considering the enriched agricultural resources of Bangladesh, biomass gasification emerges as the most advantageous method for hydrogen production. Compared to other methods like steam reforming and electrolysis, biomass gasification offers significant cost advantages. Furthermore, being an overpopulated country generates significant organic waste annually. The mismanagement of these wastes creates problematic situations for both lives and surroundings. This review approaches the way of waste management and hydrogen production and additionally discusses the current scenario, several hydrogen production pathways, utilization, and storage. This study focused on hydrogen production and utilization in Bangladesh, which will help the researchers to identify suitable and cost-effective methods to obtain the decarbonization goal in the energy sector.